Microsoft Defender for Cloud cookbook : protect multicloud and hybrid cloud environments, manage compliance and strengthen security posture /: protect multicloud and hybrid cloud environments, manage compliance and strengthen security posture. (2022) - Kranjac, Sasha
No abstract available